Soil properties and sulfur-oxidizing bacterial diversity in response to different planting patterns of shallot (Allium ascalonicum) - Muhammad Juwanda; SAKHIDIN; SAPARSO; KHARISUN (Society for Indonesian Biodiversity, 2020)
Abstract. Juwanda M, Sakhidin, Saparso, Kharisun. 2020. Soil properties and sulfur-oxidizing bacterial diversity in response to different planting patterns of shallot (Allium ascalonicum). Biodiversitas 21: 2832-2839. Sulfur is one of the primary elements required by plants for growth and development. Sulfur-oxidizing bacteria (SOB) can oxidize sulfur to sulfate, which is directly taken up by plant roots. This study aims to evaluate the soil properties and SOB diversity in various shallot planting patterns, i.e. PP1 (shallot-dry season-shallot-shallot), PP2 (shallot-dry season-shallot-rice), and PP3 (shallot-pulses-shallot-rice). Soil samples were collected from the rhizosphere of the shallot plant and analyzed for the soil properties based on the standard methods. Bacteria isolation was cultured on Starkey broth and Starkey agar. Bacteria isolate was identified based on the 16S rRNA gene sequence and compared to the GenBank database. The results showed that shallot planting patterns influence soil properties and SOB diversity. The highest content of sulfate (41.31 ppm), organic C (0.957 %), organic matter (1.650%), C/N ratio (9.57), and SOB diversity was obtained in PP3 planting pattern. Three bacterial strains have been successfully isolated i.e. A-3245D, B-3246F, and C-3247C with their closest related to Burkholderia cepacia, Klebsiella variicola, and Klebsiella aerogenes, respectively. The highest diversity and population density of SOB was in the PP3 planting patterns, i.e Burkholderia cepacia (7.45 x 105 CFU/mL); Klebsiella variicola (1.79 x 107 CFU/mL; Klebsiella aerogenes: 3.9 x 106 CFU/mL). K. variicola can be found in three planting patterns of shallot.